2016
DOI: 10.3238/arztebl.2016.0347
|View full text |Cite|
|
Sign up to set email alerts
|

The Cardiovascular Effect of Musical Genres

Abstract: Music by Mozart and Strauss lowered the subjects' blood pressure and heart rate, while music by ABBA did not. Mozart's music had the strongest effect; the piece used was his Symphony No. 40 in g minor (KV 550).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
14

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 25 publications
1
23
0
14
Order By: Relevance
“…But it is in these people that the telomere length tends to reduce faster, accelerating the aging process in this way (Steptoe et al, 2017). When listening to Mozart's 40th symphony, blood pressure significantly decreased, which was not the case when listening to ABBA music; however, the level of cortisol in the blood decreased in both cases (Trappe, Voit, 2016). Since high levels of cortisol tend to reduce telomerase activity (Choi et al, 2008), we can assume that listening to Mozart's music can positively influence telomerase activity (as it was demonstrated above).…”
Section: Discussionmentioning
confidence: 97%
“…But it is in these people that the telomere length tends to reduce faster, accelerating the aging process in this way (Steptoe et al, 2017). When listening to Mozart's 40th symphony, blood pressure significantly decreased, which was not the case when listening to ABBA music; however, the level of cortisol in the blood decreased in both cases (Trappe, Voit, 2016). Since high levels of cortisol tend to reduce telomerase activity (Choi et al, 2008), we can assume that listening to Mozart's music can positively influence telomerase activity (as it was demonstrated above).…”
Section: Discussionmentioning
confidence: 97%
“…Heart Rate: A decrease in heart rate was shown in four studies where participants experienced a lower heart rate while receiving ML compared to control groups (p<0.001, p=0.017, p<0.05, p=0.023, and p<0.05, respectively) [13,19,23,24]. Trappe et al showed that different types of music all lead to a decrease in heart rate [13], whereas Karageorghis et al found that faster tempo music actually had the opposite effect with fast, stimulative music inhibiting the return of heart rate toward resting levels [24]. One study found no significant difference in heart rate between the ML group and the control silence group [25].…”
Section: Biomarkers Of Stress Associated With Musicmentioning
confidence: 98%
“…Reviewed studies included 4 main music interventions: A) Music Listening (ML, 10 studies) is the active or passive action of listening to vocal and/or instrumental sounds combined and organized by using rhythm, melody or harmony [6,13,[19][20][21][22][23][24][25]27]. B) Meditational Music (MM, 3 studies) combines elements of mindfulness meditation, yoga movements and relaxation with music, using repetitive rhythmic sequences [15,18,26].…”
Section: Music Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that noise in hospitals negatively affects the patient's recovery (Mazer, 2010), the development of preterm infants in neonatal intensive-care units (NICU) (Gilad and Arnon, 2010), and patient care and causes stress reactions among patients in emergency departments (ED) (Short et al, 2010). In contrast, silence was found to lower the diastolic blood pressure, heart rate, and breathing rate and to decrease cortisol levels (Bernardi et al, 2006;Trappe and Voit, 2016). Listening to slow or meditative music led to even greater relaxation if combined with randomly-inserted pauses (Bernardi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%